2011
DOI: 10.1039/c0mt00104j
|View full text |Cite
|
Sign up to set email alerts
|

Probing the viral metallome: searching for metalloproteins in bacteriophage λ– the hunt begins

Abstract: Although the proteome and genome of bacteriophages are well developed, there is little knowledge about metals and their interactions with the phages, even though metals have been observed in stabilizing phage particles. With expanding studies of phage display and its promising applications, metalloprotein investigations in the bacteriophage areas are necessary to understand whether or not metalloproteins are included in the viral coat proteome. Since these virus studies are still in their infancy, lambda phage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…The limiting problem in applying LA-ICP-MS or other analytical means to detect elements in metallo-proteomic studies has been recognized as the lack of reliable methods to separate the proteome with high resolution while retaining bound metal ions, particularly in the final electrophoresis preceding metal analysis. 13,[49][50][51][52][53][54][55][56][57][58] Others have described methods with modified modifications of conditions of protein electrophoresis that seek to ameliorate the denaturing feature of SDS-PAGE. 15,[59][60][61][62] In regards to the field of metallomics, Finney et al showed the deletion of EDTA to the electrophoretic buffers of SDS-PAGE helped maintain a stable chromium-bovine serum albumin complex as measured by synchrotron X-ray fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…The limiting problem in applying LA-ICP-MS or other analytical means to detect elements in metallo-proteomic studies has been recognized as the lack of reliable methods to separate the proteome with high resolution while retaining bound metal ions, particularly in the final electrophoresis preceding metal analysis. 13,[49][50][51][52][53][54][55][56][57][58] Others have described methods with modified modifications of conditions of protein electrophoresis that seek to ameliorate the denaturing feature of SDS-PAGE. 15,[59][60][61][62] In regards to the field of metallomics, Finney et al showed the deletion of EDTA to the electrophoretic buffers of SDS-PAGE helped maintain a stable chromium-bovine serum albumin complex as measured by synchrotron X-ray fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also documented that the oxidation and oxidative stress such as the addition of peroxide or ascorbate could enhance the biocidal properties of copper 63 . Cu ions can also interact with different viral components, e.g., can cause the inactivation of viral metalloproteins 64,65 by replacing the respective metal with copper 66 . Proteins tend to select divalent metal ions from the environment, following the Irving-Williams order of stability: 67 Mg 2+ < Mn 2+ < Fe 2+ < Co 2+ < Ni 2+ < Cu 2+ > Zn 2+ .…”
Section: Review Articlementioning
confidence: 99%
“…В связи с этим следует отметить принципиальные различия молекулярных форм усвоения металла представителями различных царств и специфику форм и механизмов усвоения в зависимости от таксонов: по этому принципу в анализе первичных ассимилянтов различают, например, металломику хемоавтотрофных микроорганизмов (Basu, 2008;Barton et al, 2007) и металломику растений (Salt, 2013). В то же время, неспецифической фиксацией металлов и, в итоге, собственной вирусной металломикой характеризуют и бактериофагов (Zhang et al, 2011), что рационально, исходя из известной связи между эпигенетикой и металломикой (Wrobel et al, 2009) и наличия содержащих их бактерий в автотрофных сообществах при некоторых формах рудообразования. Характеристической чертой множества подходов металломики является их применимость к палеобиогенному веществу (Edwards et al, 2014), что позволяет говорить об аккумуляционной достоверности данных металломики в аспекте построения палеогеологических карт при учете информации об отсутствии метаморфизирующей активности современных организмов на некотором уровне или регионе интереса (ROI).…”
Section: месторождения стратегических и редкоземельных металлов как предмет биоиндикации элементологии и металломикиunclassified